Comparison of posterior pharyngeal wall and nasopharyngeal swabbing as a means of detecting the carriage of Neisseria meningitidis in adolescents - Esposito, S.; Zampiero, A.; Terranova, L.; Montinaro, V.; Peves Rios, W.; Scala, A.; Ansuini, V.; Galeone, C.; Principi, N. (European journal of clinical microbiology & infectious diseases, 2013)
The purpose of this investigation was to evaluate the effectiveness of posterior pharyngeal and nasopharyngeal swabs in identifying and quantifying meningococcal carriage. Two swab samples were obtained from 564 healthy adolescents aged 15–19 years, the first taken from the posterior pharyngeal wall through the mouth and the second through the nose. Bacterial genomic DNA was extracted and screened for Neisseria meningitidis by means of two separate singleplex real-time polymerase chain reactions (real-time PCRs) in order to identify the CtrA and sodC genes. Subsequently, N. meningitidis -positive samples underwent a further singleplex real-time PCR in order to determine the N. meningitidis serogroup, and the DNA was quantified by means of standard curves. Thirty-seven subjects (6.6 %) were found to be carriers of N. meningitidis . The most frequently carried serogroup was serogroup B (15 cases, 40.5 %); serogroups A, Y, X, W135 and Z were found in, respectively, two (5.4 %), five (13.5 %), four (10.8 %), three (8.1 %) and one subject (2.7 %); the serogroup was not identified in seven cases. The detection of carrier status was significantly more frequent using posterior pharyngeal swabs (5.3 % vs. 2.1 %; p = 0.004), which also contained a significantly larger number of N. meningitidis genomic copies (4.91 ± 1.39 vs. 2.50 ± 0.8 log 10 genomic copies/mL; p < 0.001). Posterior pharyngeal swabs seem to be better than nasopharyngeal swabs for detecting N. meningitidis carriage in large-scale epidemiological studies because they identify a significantly larger number of pathogen carriers and recover a significantly larger amount of bacterial DNA.